Pemanfaatan Dana Bantuan Operasional Kesehatan (BOK) Dan Implikasinya Terhadap Peningkatan Pelayanan Pada Pukesmas Rawat Inap Di Kabupaten Lima Puluh Kota - Mimi Hanggraini; Asdi Agustar; Jafrinur (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
This study aims to determine the allocation of the use of Health Operational Assistance (BOK) funds at the Dangung-Dangung Health Center in Lima Puluh Kota Regency and to determine the implications of the Health Operational Assistance (BOK) funds for Maternal and Child Health services at Inpatient Health Centers in Lima Puluh Kota Regency. .The research was conducted using the case study method. In this case, the case is the Dangung Dangung Health Center, which is one of the 6 Outpatient Health Centers in Fifty Cities District.For this reason, data analysis and its interpretation were carried out in this study, namely: (1) category collection, describing in an effort to find a collection of data examples and hoping to find meaning that is relevant to the issue to be explained; (2) direct interpretation, to look at an example and draw meaning from it.The results showed thatBOK funds have not been fully utilized, which every year there are still funds that have not been fully realized, this is due to several things: Human resources, policies and others.The impact of providing assistance for efforts to improve MCH through programs financed by the BOK has not been running smoothly, this is due to the long disbursement of the BOK budget, and it is felt that it is quite difficult for the Puskesmas, so that many of the planned programs are disrupted in their implementation..